The Influence of the Effectiveness the Implementation of the Presence Administrative Information System on Work Discipline and its Impact on the Quality Employee Service at SDN 160 Sukalaksana Bandung City - Abudin, Desi Nuraeni; Priyatna, Soeganda; Susniwati, Susniwati (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This research aims to find out whether the attendance administration information system has an effect on employee work discipline and its impact on the quality of employee service at SDN 160 Sukalaksana, Bandung City. The independent variable is the presence administration information system, the intervening (mediation) variable, namely employee work discipline, and the dependent variable, namely employee service quality. This type of research is included in quantitative research, while the research methods used are descriptive and verification methods. The population in this study were civil servants (PNS) and parents of students at SDN 160 Sukalaksana, Bandung City, totaling 47 respondents. The sampling technique is non-probability sampling using saturated samples, so the total sample is 47 respondents. The data analysis used in this research is path analysis using SPSS software. The results of the research show that the effectiveness of implementing the attendance administration information system has a direct effect on employee work discipline, the effectiveness of implementing the attendance administration information system has no direct effect on the quality of employee service, employee work discipline has a direct effect on the quality of employee service, and the effectiveness of implementing the administration information system Presence has an indirect effect on the quality of employee service through employee work discipline.